Establishing a probabilistic reversal learning test in mice: Evidence for the processes mediating reward-stay and punishment-shift behaviour and for their modulation by serotonin - Ineichen, Christian; Sigrist, Hannes; Spinelli, Simona; Lesch, Klaus-Peter; Sautter, Eva; Seifritz, Erich; Pryce, Christopher R. (Neuropharmacology, 2012)
Valid animal models of psychopathology need to include behavioural readouts informed by human findings. In the probabilistic reversal learning (PRL) task, human subjects are confronted with serial reversal of the contingency between two operant stimuli and reward/punishment and, superimposed on this, a low probability (0.2) of punished correct responses/rewarded incorrect responses. In depression, reward-stay and reversals completed are unaffected but response-shift following punished correct response trials, referred to as negative feedback sensitivity (NFS), is increased. The aims of this study were to: establish an operant spatial PRL test appropriate for mice; obtain evidence for the processes mediating reward-stay and punishment-shift responding; and assess effects thereon of genetically- and pharmacologically-altered serotonin (5-HT) function. The study was conducted with wildtype (WT) and heterozygous mutant (HET) mice from a 5-HT transporter (5-HTT) null mutant strain. Mice were mildly food deprived and reward was sugar pellet and punishment was 5-s time out. Mice exhibited high motivation and adaptive reversal performance. Increased probability of punished correct response (PCR) trials per session (p = 0.1, 0.2 or 0.3) led to monotonic decrease in reward-stay and reversals completed, suggesting accurate reward prediction. NFS differed from chance-level at p PCR = 0.1, suggesting accurate punishment prediction, whereas NFS was at chance-level at p = 0.2–0.3. At p PCR = 0.1, HET mice exhibited lower NFS than WT mice. The 5-HTT blocker escitalopram was studied acutely at p PCR = 0.2: a low dose (0.5–1.5 mg/kg) resulted in decreased NFS, increased reward-stay and increased reversals completed, and similarly in WT and HET mice. This study demonstrates that testing PRL in mice can provide evidence on the regulation of reward and punishment processing that is, albeit within certain limits, of relevance to human emotional-cognitive processing, its dysfunction and treatment. ► Depressed patients exhibit deficits in probabilistic reversal learning (PRL). ► A PRL paradigm was developed for C57BL/6 mice. ► Operant responding was sensitive to probability of punished correct responses (PCR). ► Heterozygous serotonin transporter mutant mice exhibited reduced sensitivity to PCR. ► Low-acute SSRI escitalopram administration also reduced sensitivity to PCR.